Prevalence of Metabolic Syndrome among Working Adults in Ethiopia - A. Tran; B. Gelaye; B. Girma; S. Lemma; Y. Berhane; T. Bekele; A. Khali; M. A. Williams (International Journal of Hypertension)
Objective. To evaluate the prevalence of metabolic syndrome (MetS) according to the International Diabetes Federation (IDF) and Adult Treatment Panel (ATP) III criteria among working East African adults. Design. This cross-sectional study of 1,935 individuals (1,171 men and 764 women) was conducted among working adults in Addis Ababa, Ethiopia. The study was conducted in accordance with the STEPwise approach of the World Health Organization. Results. According to ATP III and IDF definitions, the overall prevalence of MetS was 12.5% and 17.9%, respectively. Using ATP III criteria, the prevalence of MetS was 10.0% in men and 16.2% in women. Application of the IDF criteria resulted in a MetS prevalence of 14.0% in men and 24.0% in women. The most common MetS components among women were reduced high-density lipoprotein-cholesterol (HDL-C) (23.2%) and abdominal obesity (19.6%); whilst reduced HDL-C concentrations (23.4%) and high blood pressure (21.8%) were most common among men. Conclusion. MetS and its individual components are prevalent among an apparently healthy working population in Ethiopia. These findings indicate the need for evidence-based health promotion and disease prevention programs; and more robust efforts directed towards the screening, diagnosis and management of MetS and its components among Ethiopian adults.